Enfermedades asociadas al sector saneamiento - Dueñas Jurado, Carlos (2022)
The well-being and good living of people depends on many environmental factors, including access to drinking water and sewerage services. The present work had the objective of determining the diseases associated with water and sanitation sector management. An exhaustive and systematic review was carried out in different sources and databases such as ScienceDirect, Scopus, PubMed, SciELO, ResearchGate, Latindex, Renati and Alicia, using keywords such as "water and health", "drinking water", "water disease", "heavy metals", "pathogenic microorganisms". As a result, it can be indicated that health risks related to contamination of water supply and sanitation systems include infections and serious and chronic diseases, since water is involved in all physiological aspects of the human being. Water contamination by chemical agents is caused by the presence of heavy metals, of which the presence of As has been highlighted in the latest research, causing affections to the vital organs of the human being, in many cases they are carcinogenic, while among the microbiological agents, fecal material is the main contaminant, causing various types of dysenteric health problems.